Implementation of Tabligh As Prophetic Leadership of Muhammadiyah Through Political Movement - Rika Eraswati; Rina Ervina; Romelah (Audito Comparative Law Journal (ACLJ), 2022)
One of the forces of civil society that is always present and makes a real contribution to the progress of Indonesian politics is the Islamic mass organization Muhammadiyah.  In order to achieve the aspired goals, the Muhammadiyah leadership model exists as the basis or ideology in achieving such goals, especially in Muhammadiyah's contribution to national legal politics. The purpose of this study is to determine the implementation of Tabligh as prophetic leadership of Muhammadiyah in its role as a political movement to influence the national political process. This paper was built based on a literature review. Indonesia is a democratic country and Muhammadiyah was born as a political movement in influencing the national political process. It is a form of citizen aspirations that was formed using an association of groups or organizations as guaranteed by the 1945 Constitution. Muhammadiyah, in their every struggle including in national politics, always uses its identity or ideology as a da'wah organization based on "amar ma'ruf nahi munkar" that is sourced from the Qur'an and Sunnah. Muhammadiyah implements the nature of Tabligh in carrying out its role as a political movement which is to always criticize any regulations that are contrary to the truth or that will bring harm to society. Muhammadiyah is not in a coalition with the government or with any political party, but Muhammadiyah has always supported policies that lead to the benefit of society.